ANALISIS IMPLIKATUR KONVENSIONAL MEME DALAM SURAT KABAR RADAR TEGAL - Cintya Nurika Irma; Eti Nurul Hikmah (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2021)
This study aims to describe the conventional impression of memes in Radar Tegal newspaper. The type of research used is qualitative research with descriptive methods because it describes the implications of memes in the Radar Tegal newspaper. The data used in this study are implied discourses on memes contained in the Radar Tegal newspaper in September and October 2019. Data collection used in this study includes collecting objects in the form of imaginary discourse contained in memes printed in newspapers and then reading one by one the discourse contained in memes so that these implicatures can be understood and identified. The technique used in this research is triangulation technique.broadcast information, educate and influence demonstration, human trafficking and terrorist events. In addition, memes in newspapers are a visual form of expression in response to an event.